2010
DOI: 10.1094/phyto-100-5-0454
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Evaluation of Resistance Responses of Potato to Different Isolates of Alternaria solani

Abstract: The resistance phenotypes of nine potato cultivars to five isolates of Alternaria solani, causal agent of early blight, were studied after inoculation and growth under greenhouse conditions. We identified potato cultivars with both susceptible and resistant phenotypes as well as A. solani isolates with varying degrees of aggressiveness. Two potato cultivars and two pathogen isolates were selected for biochemical analysis of phenol production and peroxidase activity after inoculation. Phenol compounds were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 25 publications
2
13
0
2
Order By: Relevance
“…1 ß-1,3- when compared to the susceptible cv. Granula (Shahbazi et al 2010). Although quantification of symptoms was not calculated, the whole plant inoculations done in these experiments confirmed these results, since cv.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…1 ß-1,3- when compared to the susceptible cv. Granula (Shahbazi et al 2010). Although quantification of symptoms was not calculated, the whole plant inoculations done in these experiments confirmed these results, since cv.…”
Section: Resultssupporting
confidence: 63%
“…Diamond was correlated with an increase in the amount of total phenols and peroxidase activity (Shahbazi et al 2010). In the present study we have shown that resistance in cv.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in peroxidase due to pathogen challenge has been previously reported [52][53][54]. Interestingly, an increase in peroxidase activity has been associated with an enhanced defense response [55][56][57]. POD is one of the vital antioxidant enzymes involved in the production of reactive oxygen species, which directly kills pathogens via its toxic effect and inhibits pathogen spread through lignin production [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…chitinases and b-1,3-glucanases) and those that create/maintain environments unsuitable for pathogens (i.e. peroxidases and polyphenol oxidases) [16,18]. Increases in polyphenol oxidase levels would result in increased browning in freshly cut potatoes as the enzyme oxidizes phenolic compounds into brown-colored products.…”
Section: Introductionmentioning
confidence: 99%